(untitled) (INTERNATIONAL JOURNAL OF COMPUTERS & TECHNOLOGY, 2018)
An asymmetric DGS consisting of two square headed slots connected transversely with a rectangular slot is etched in the ground plane underneath a high-low impedance microstrip line.Â It provides a band-reject filtering characteristics with sharp transition. Thus, it may be modeled as m-derived filter section. Accordingly, T-type LC equivalent circuit is proposed and LC parameters are extracted. A planar composite lowpass filter is designed by image parameter method and implemented by different DGS units. A composite filter requires at least three filter sections, of which two m-derived sections and one constant k-section. In proposed scheme, one such m-derived section is directly replaced by proposed DGS unit, whose cut-off frequency is same as that of designed m-derived section. The other m-derived section implemented by proposed DGS unit divided into equivalent two L-sections which will act as a termination for impedance matching. A constant k-section has been realized by a dumbbell shaped DGS having same cutoff frequency. Here lumped LC parameters are directly replaced by the equivalent LC values of the DGSs and therefore, produce almost ideal filter characteristics by overcoming the limitations of microstrip technology.